HUBUNGAN KECERDASAN EMOSIONAL DENGAN STRESS COPING SISWA DALAM BELAJAR KELAS XI SMA SEMEN PADANG SEMESTER GENAP TAHUN AJARAN 2026/2027 - Mutia Setiawan, Cindy; Rini Sefriani; Linda Fitria (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The Relationship between Emotional Intelligence and Students’ Stress Coping in Learning among Eleventh Grade Students of SMA Semen Padang in the 2026/2027 Academic Year. Thesis. Guidance and Counseling Study Program, Faculty of Teacher Training and Education, Universitas Putra Indonesia “YPTK” Padang. This study was motivated by the importance of students’ ability to manage academic stress during the learning process. Emotional intelligence is assumed to play an important role in determining the stress coping strategies used by students. This research aimed to determine the relationship between emotional intelligence and stress coping among eleventh grade students of SMA Semen Padang in the 2026/2027 academic year. This study employed a quantitative approach with a descriptive correlational design. The population consisted of 134 students, and 65 students were selected as the sample using simple random sampling technique. The research instrument was a Likert-scale questionnaire consisting of 40 statement items. Data were analyzed using normality test, linearity test, and Pearson Product Moment correlation test with the help of SPSS 24. The results showed that there was a significant relationship between emotional intelligence and students’ stress coping, with a correlation coefficient of 0.726 and a significance value of 0.000 (p < 0.05). This indicates that the higher the students’ emotional intelligence, the better their stress coping ability in learning. Therefore, it can be concluded that emotional intelligence has a positive and significant relationship with stress coping among eleventh grade students of SMA Semen Padang.